Risk of ischaemic stroke among new users of glucosamine and chondroitin sulphate: a nested case–control study. (July 2022) - Mazzucchelli, Ramón; Rodríguez-Martín, Sara; Crespí-Villarías, Natalia; García-Vadillo, Alberto; Gil, Miguel; Izquierdo-Esteban, Laura; Rodríguez-Miguel, Antonio; Barreira-Hernández, Diana; Fernández-Antón, Encarnación; García-Lledó, Alberto; Pascual, Aina; Vitaloni, Marianna; et al.
Background: Several studies have reported that the use of chondroitin sulphate (CS) and glucosamine may reduce the risk of acute myocardial infarction. Although it is thought that this potential benefit could be extended to ischaemic stroke (IS), the evidence is scarce. Objective: To test the hypothesis that the use of prescription glucosamine or CS reduces the risk of IS. Design: Case–control study nested in an open cohort. Methods: Patients aged 40–99 years registered in a Spanish primary healthcare database (BIFAP) during the 2002–2015 study period. From this cohort, we identified incident cases of IS, applying a case-finding algorithm and specific validation procedures, and randomly sampled five controls per case, individually matched with cases by exact age, gender and index date. Adjusted odds ratios (AORs) and 95% confidence interval (CI) were computed through a conditional logistic regression. Only new users of glucosamine or CS were considered. Results: A total of 13, 952 incident cases of IS and 69, 199 controls were included. Of them, 106 cases (0.76%) and 803 controls (1.16%) were current users of glucosamine or CS at index date, yielding an AOR of 0.66 (95% CI: 0.54–0.82) (for glucosamine, AOR: 0.55; 95% CI: 0.39–0.77; and for CS, AOR: 0.77; 95% CI: 0.60–0.99). The reduced risk among current users was observed in both sexes (men, AOR: 0.69; 95% CI: 0.49–0.98; women, AOR: 0.65; 95% CI: 0.50–0.85), in individuals above and below 70 years of age (AOR: 0.69; 95% CI: 0.53–0.89 and AOR: 0.59; 95% CI: 0.41–0.85, respectively), in individuals with vascular risk factors (AOR: 0.53; 95% CI: 0.39–0.74) and among current/recent users of nonsteroidal anti-inflammatory drugs (NSAIDs) (AOR: 0.71; 95% CI: 0.55–0.92). Regarding duration, the reduced risk was observed in short-term users (<365 days, AOR: 0.61; 95% CI: 0.48–0.78) while faded and became nonsignificant in long-term users (>364 days AOR: 0.86; 95% CI: 0.57–1.31). Conclusions: Our results support a protective effect of prescription CS and glucosamine in IS, which was observed even in patients at vascular risk. Mini abstract: Our aim was to analyse whether the use of glucosamine or chondroitin sulphate (CS) reduces the risk of ischaemic stroke (IS). We detected a significant decrease.